Employee Performance Model Through Job Satisfaction: Analysis of Work Environment and Competence (Study at the Public Works and Spatial Planning Department of Tanjung Jabung Timur Regency) - Junaidi Junaidi; Hapzi Ali; Maya Maria (Dinasti Publisher, 2025)
This study aims to analyze the influence of work environment and competence on employee performance both directly and indirectly through work satisfaction at the Public Works and Spatial Planning (PUPR) Department of East Tanjung Jabung Regency. The population in this study were 72 employees. This study used a census method where all employees were used as research samples. This study used a quantitative approach with a survey method and used Partial Least Square (PLS) data analysis. The results of the study indicate that work environment and competence have an influence on employee performance, both directly and indirectly through employee job satisfaction. This explains that if the PUPR Department of East Tanjung Jabung Regency has a conducive work environment, and is also supported by a good level of employee competence, this will cause employees to be more satisfied in their work, working optimally in the organization.